Structural and transport properties of Bi-substituted Co2MnO4 - ARORA, SUNIL KUMAR; SHVETS, IGOR (American Physical Society, 2009)
We report the structural and transport properties of the Bi-substituted Co2MnO4 multiferroic materials. Samples synthesized using the solid state reaction route with the composition BixCo2?xMnO4 (<0x<0.3) exhibit a single phase behavior with a cubic spinel structure (space group Fd3m). The lattice parameter was found to increase with the Bi substitution. The dc-conductivity studies reveal that all the samples possess a semiconducting behavior. The resistivity was found to decrease with the increase in the Bi substitution. The dc- as well as ac-conductivity data were analyzed in the light of various conduction models. The dc-conductivity data are explained using the variable range hopping model. The ac conductivity calculated from the dielectric data as a function of temperature and frequency demonstrates the cross over from small polaron tunneling to correlated barrier hopping type conduction in these materials.
Journal of Applied Physics
53rd Annual Conference on Magnetism and Magnetic Materials, NOV 11-14, 2008 Austin, TX
PUBLISHED
Austin, Texas, USA
Keywords: Atomic, molecular and chemical physics; Co2MnO4